International climate diplomacy after the Trump election victory: Germany and the EU should intensify their outreach to climate allies - Susanne Dröge (Stiftung Wissenschaft und Politik (SWP), 2016)
The election of Donald Trump as the new US president heralds difficult times for international climate policy. The US together with the EU was the key driver of the Paris Agreement in 2015. The new president will end climate policy cooperation with China, and with other emerging and developing countries. Moreover, he has announced plans to reverse the climate-policy legislation which is needed to implement the US climate targets. This will undermine the trust many countries have increasingly put in the US as a credible climate policy partner who is serious about tackling global warming. German and EU negotiators know this challenging situation from the years after the Bush administration's withdrawal from the Kyoto Protocol in 2000. In light of the enormous push for international climate policy cooperation over the past three years, Germany and the EU need a comprehensive new climate diplomacy strategy to deal with the fallout of the US turnaround. First of all, they need to prevent a chain reaction at the international level by pushing, together with their key partners, for the Paris Agreement to be implemented. Second, they will have to pay more attention to how they interact with the new US representatives joining the negotiations as well as with the new US administration. And third, they should limit the damage to climate diplomacy and action by cooperating even more closely with US states and non-state actors. (SWP Comments)
Keywords: 320